2003
DOI: 10.1111/1541-1338.d01-7
|View full text |Cite
|
Sign up to set email alerts
|

Family Leave Policies and Labor Market Segregation in Germany: Reinvention or Reform of the Male Breadwinner Model?1

Abstract: The historically dominant male breadwinner and female carer model in West Germany has resulted in comparably low female employment rates and a gender-structured labor market. Since the 1970s, the decline of traditional patterns and sectors of male employment has been accompanied by the expansion of the female-dominated service sector. Supplemented by women's higher educational attainment, a pluralism of household forms, and German unification, the result has been constant growth in female employment. With more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…No previous work requirements are needed to qualify for the homecare allowance, but the other adult in the household (parent or new partner) must be in employment or enrolled in education. The conclusions from other countries with homecare allowances are that such benefits are mainly used by women with low education, increasing the risks for marginalization in relation to the labor market (84,85). Similar outcomes have also been found in the other Nordic countries where homecare leave was introduced in family policy models otherwise oriented to sustaining earner-carer families (44,86,87).…”
Section: The Earner-carer Model At the Crossroads: Family Policy Refosupporting
confidence: 58%
“…No previous work requirements are needed to qualify for the homecare allowance, but the other adult in the household (parent or new partner) must be in employment or enrolled in education. The conclusions from other countries with homecare allowances are that such benefits are mainly used by women with low education, increasing the risks for marginalization in relation to the labor market (84,85). Similar outcomes have also been found in the other Nordic countries where homecare leave was introduced in family policy models otherwise oriented to sustaining earner-carer families (44,86,87).…”
Section: The Earner-carer Model At the Crossroads: Family Policy Refosupporting
confidence: 58%
“…Longer leaves should also decrease women's employment probability because career breaks decrease women's market human capital (Baum 2002;Gupta and Smith 2002). 1 (Gottschall and Bird [2003] have shown that in countries where longer leaves are available, women take on average longer leaves.) Women's returns from employment in these countries should decrease even more, because employers may perceive them more strongly as temporary employees (Avdeyeva 2006), which would lower women's chances of promotion, and hence, lower their earnings.…”
Section: Country-level Modelmentioning
confidence: 99%
“…7 It is therefore useful to restrict the sample for the analysis to those women who would -potentially -be entitled to the full payment of maternity benefits as it can be assumed that employers would find it more likely that women with lower salaries would have a higher propensity to take (longer) leave. Evidence shows that indeed except for women with higher education German women took the full leave period of 3 years (Gottschall and Bird 2003, Büchel and van Ham 2004, Schönberg and Ludsteck 2014. As a consequence, women with a high level of education probably did not experience the same reduction in the probability of becoming hired.…”
Section: Data and Econometric Considerations 21 Data: The German Socmentioning
confidence: 99%
“…[ Extended periods of leave and enhanced dismissal protection only applied to mothers and in Germany almost exclusively the women took maternity leave (Gottschall and Bird 2003), thus restricting the group of the labour force affected by the reform to women who could (potentially) give birth. Therefore, employers' expectations should have mainly changed about women in childbearing age since these were potentially covered by the reforms.…”
Section: Identification: Changes Of Maternity Leave Legislationmentioning
confidence: 99%